How Muslims-Christians-Jews Relations in the Qur’an? (Critical Interpretation of Q. al-Baqarah/2:120 Using Maʻnā-cum-Magzā Approach) - Abdul Muiz Amir, (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2022)
This article seeks to interpret Q. al-Baqarah/2:120 that is consistently referred by textual-literalism groups of Muslims as preserved in classical commentaries books. Their understanding raises hatred towards the Jews and the Christians, which eventually leads to intolerance acts. The question to be answered by this article is how the maʻnā-cum-magzā approach could become an alternative method in understanding the verse, so it promotes an inclusive attitude towards the Jews and the Christians? This qualita-tive study works under the deconstructivism paradigm. The result of the study shows that the classical understanding of Q. 2:120 leads to theologically normative discourse, from which the legitimation of eternal and universal hatred against the Jews and the Christians finds its base. The maʻnā-cum-magzā approach, on the other hand, suggests that the verse should be situated in its specific socio-political context. Therefore, the Jews and the Christians mentioned by the verse refer specifically to the Jews of Medina and the Christians of Najran for their abuse of religion as the source of legitimacy for their political hegemony. The academic contribution of this study is, therefore, to pro-duce an alternative interpretation that distances the verse from the justification for hatred based on religious credentials.